AMBIVALENSI NASIONALISME DALAM CERPEN “CLARA ATAWA WANITA YANG DIPERKOSA” KARYA SENO GUMIRA AJIDARMA: KAJIAN POSKOLONIAL - Arif Kurniar Rakhman (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Nationalism produces a complex identity because it is constructed from colonial tradition which is reproduced continuously by history. In this context, the writer of this paper analyzes the phenomenon from literary approach. A short story written by Indonesian author, Seno Gumira Ajidarma, entitled “Clara atawa Wanita yang Diperkosa” is chosen because it reveals a different narration in viewing the existence of Chinese Society in Indonesia. This paper will use post-colonial study to reveal how is the rhetoric of tradition and development, the idea of universality and postnation, also the ambivalence in nationalism discourse.Keywords: nationalism, Chinese, post-colonial, ambivalence.